an Analysis of the Application of Multicultural Education for Senior High School Students at the Sultan Iskandar Muda Foundation in Combating Interfaith Intolerance - Siburian, Thereza Dwi Ningrum; Simbolon, Boy Dippu Tua; Septianda, Rama Rizky; Situmorang, Lennai; Wahyuni, Devi Sri; Sihaloho, Oksari Anastasya (Pusdikra Publishing, 2024)
This research aims to analyze the implementation of multicultural education at the Sultan Iskandar Muda Education Foundation High School (YPSIM) in an effort to combat attitudes of interreligious intolerance among students. Multicultural education at YPSIM is implemented through a learning approach that integrates the values of tolerance, respect for diversity and mutual respect. The research methods used were observation, interviews and questionnaires involving school principals, teachers and students as respondents. The research results show that school principals play an active role in formulating policies that support inclusion, provide worship facilities for various religions, and involve the community to strengthen multicultural values. Support from the foundation, diversity of students and staff, and parent participation are strong supporting factors. However, several challenges such as conservative perceptions from outside the school, limited teacher training, and limited facilities hinder the optimal implementation of multicultural education. Overall, this research shows that the implementation of multicultural education at YPSIM contributes to reducing attitudes of interreligious intolerance in schools. This research recommends the implementation of multicultural education in other schools to form tolerant and inclusive student characters.